Ceftriaxone-induced encephalopathy in a patient with a solitary kidney - Yuya Futagi; Yuriko Ito; Junya Nakade; Arimi Fujita; Tsutomu Shimada; Misaki Yoshida; Yoshinori Takahashi; Mitsuhiro Kawano; Takumi Taniguchi; Yoshimichi Sai (International Journal of Infectious Diseases, 2022)
Ceftriaxone (CRO) is a long-acting third-generation cephalosporin antibiotic. We present a case of CRO-induced encephalopathy in an 84-year-old male patient with a solitary right kidney, admitted with bilateral pneumonia and right pyelonephritis. Intravenous CRO (2 g, every 24 hours) was started for the infection, but tonic-clonic seizures of the left face and left upper extremity appeared on the eighth day. To examine the relationship between CRO administration and the seizures, we measured CRO concentrations in the patients’ plasma/serum and cerebrospinal fluid. The CRO concentration in blood at the onset of encephalopathy was estimated to have been approximately 60 μg/ml based on a simulation curve. We also calculated the pharmacokinetic parameters after CRO administration. The patient had about one-tenth of the total body clearance and one-third of the volume of distribution compared with healthy adults, and the elimination half-life was about three times longer.